(untitled) (Research, Society and Development, 2022)
The music of viola caipira became a means of cultural recording, transmitting moral and ethical teachings to listeners and can be used as a tool for educational practices. Music promotes a pleasant assimilation in the learning process, so Environmental Education, due to its interdisciplinary character, can use country music to form responsible citizens from a socio-environmental point of view. The present work aimed to sensitize students to environmental issues through lyrics and country music at the Quim Machado Municipal School in Itumbiara, Goiás, Brazil. Sixty-seven students were selected, from the 6th to the 9th grade, who were encouraged to interact with moda de viola through the production of country music lyrics with the environmental theme. Most of the compositions were made in duos or trios, resulting in 27 parodies. From the awareness of environmental issues through the viola caipira, the students were able to produce song lyrics poetically portraying the environmental disturbances observed in their surroundings. Concern about water resources and deforestation were the most mentioned subjects in the songs, followed by verses referring to appreciation and respect for nature. The production of the songs allowed a playful activity associating the knowledge of the Portuguese Language and Sciences with music, art, culture and environment, validating this experience as a productive tool for Environmental Education.